Quantitative analysis of the economic characteristics of the land transport network - العنبكي, د.هادي عبدالمحسن; نهير, د.عادل; فليح, م.د.مهيب كامل (Journal of Planner and Development, 2009)
Highway network could be considered as a function of the developmental level of the region, that it is representing the sensitive nerve of the economic activity and the corner stone for the implementation of development plans and developing the spatial structure. The main theme of this thesis is to show the characteristics of the regional highway network of Anbar and to determine the most important effective spatial characteristics and the dimension of that effect negatively or positively. Further this thesis tries to draw an imagination for the connection between highway network as a spatial phenomenon and the surrounded natural and human variables within the spatial structure of the region. This thesis aiming also to determine the nature of the regional highway of Anbar, how it has been developed, what are its characteristics, types, and patterns that have been came from the spatial differentiation in the region to evaluate it spatially and as an indicator for the socio-economic development in   the study area.